Polska i węgierska droga do demokracji w perspektywie porównawczej - Pawlak, Agnieszka (Acta Universitatis Lodziensis. Folia Historica, 2005)
Text concerns the post-war history of these two countries under the protectorate of USRR, the changing social reception of communism, their fight for democracy and respectable life. The text focuses on Polish post-war history, especially the facts having influenced the Round Table negotiations and beginning of transition processes. Detailed analysis tries to explain the difference between Polish and Hungarian ways to democracy, especially why Hungarians experienced tragic revolution and Soviet armed intervention whereas Polish protests were more peaceful. Also social consequences of 1956 year varied in both countries: the Polish regularly protested against the communist party, whereas Hungarians chose the compromise. However, finally in 1989 both Poland and Hungary became leaders of transition process in Central-Eastern Europe.